El bien jurídico protegido en los tipos penales relativos a las formas contemporáneas de esclavitud - Rodríguez Vásquez, Julio Alberto (2025)
This article identifies and evaluates the different positions that have been raised in international criminal doctrine regarding the legal interests protected by the criminal offenses related to contemporary forms of slavery. In this sense, the strengths and weaknesses of the following proposals are analyzed: freedom, dignity, moral integrity, multi-offensiveness and legal personality. This evaluation is carried out on the basis of understanding that the legal interest provides the offense legitimacy and, at the same time, is a dogmatic category that contributes to the teleological interpretation, avoiding the problems of “underinclusion” and reducing those of “overinclusion”.Furthermore, special consideration is given to the fact that the injustice of contemporary forms of slavery lies in the severe objectification of the human being, which uses the intense control exercised over the victim. The main conclusion of this analysis is that there are material and practical reasons to maintain that dignity is the legal good protected by these crimes.